Performance Comparison of Loop Source and Grounded-Wire Source for Shallow Refined TEM Detection - Zhengyu Xu; Guofeng Zhao; Jiangying Peng; Xiao Ma; Wei Liu (IEEE Access)
Loop-source transient electromagnetic method (TEM) and grounded-wire-source TEM are two of the most popular methods in geological electromagnetic detection. Advances in power electronics have made it possible to achieve high magnetic moments by transmitting large current pulses through small excitation coils, enabling the use of independent loop sources as magnetic dipoles in active detection techniques. The independent loop source, by overcoming the attenuation of the magnetic field caused by distance, becomes an efficient and low-cost tool for shallow detection. Both the independent loop source and the grounded-wire source share similarities in detection principles and scanning modes. This paper discusses the merits and shortcomings of the loop source and grounded-wire source for shallow, multiscale refined detection. The three-dimensional model is established and the electromagnetic response characteristics are compared by COMSOL finite element simulation software. Additionally, the influence of anomalous burial depth, offset distance, and measurement height on the detection results of these two near-source methods are thoroughly discussed. Finally, it is explained by the field measurement results. The comparison of simulation and experimental results shows that the loop-source TEM is more suitable for shallow refined detection in terms of response quality and construction efficiency.